Cost And Time Analysis of Drainage Works Using Conventional Riverstone Method and Precast U-Ditch Method - Yulianus Brechmans Dilianto; Galuh, Dimas Langga Chandra; Sutrisno, Widarto (Journal of Green Science and Technology, 2024)
The aim of this research is to determine the comparison of costs and work time using the conventional river stone method and the precast u-ditch method. So from the two methods mentioned above, we can choose or compare which method can provide benefits in terms of cost and time. This research uses a quantitative method, which explains a process of finding knowledge using data in the form of numbers as a tool for analyzing information about what you want to know in a situation that is the object of study and then analyzed. Comparative analysis of costs and time for drainage channel work using the conventional method with a length of 192 meters takes 55 working days with a cost of Rp 123,617,000.0 while the precast method with a length of 174 meters takes 48 working days with a cost of Rp 78,292,000.0 . The conventional method takes 14% longer to carry out work compared to the precast method. The cost per meter of work using the conventional method is Rp 6,438,385, while work using the method is Rp 4,449,540 with a difference of Rp 1,988,845. The use of precast methods is 30% lower than conventional methods.